Gonadotropin-releasing hormone agonist use in men without a cancer registry diagnosis of prostate cancer - Kuo Yong-fang; Goodwin James S; Shahinian Vahakn B (BMC, 2008)
Abstract Background Use of gonadotropin-releasing hormone (GnRH) agonists has become popular for virtually all stages of prostate cancer. We hypothesized that some men receive these agents after only a limited work-up for their cancer. Such cases may be missed by tumor registries, leading to underestimates of the total extent of GnRH agonist use. Methods We used linked Surveillance, Epidemiology and End-Results (SEER)-Medicare data from 1993 through 2001 to identify GnRH agonist use in men with either a diagnosis of prostate cancer registered in SEER, or with a diagnosis of prostate cancer based only on Medicare claims (from the 5% control sample of Medicare beneficiaries residing in SEER areas without a registered diagnosis of cancer). The proportion of incident GnRH agonist users without a registry diagnosis of prostate cancer was calculated. Factors associated with lack of a registry diagnosis were examined in multivariable analyses. Results Of incident GnRH agonist users, 8.9% had no diagnosis of prostate cancer registered in SEER. In a multivariable logistic regression model, lack of a registry diagnosis of prostate cancer in GnRH agonist users was significantly more likely with increasing comorbidity, whereas it was less likely in men who had undergone either inpatient admission or procedures such as radical prostatectomy, prostate biopsy, or transurethral resection of the prostate. Conclusion Reliance solely on tumor registry data may underestimate the rate of GnRH agonist use in men with prostate cancer.